Effectiveness of Therapy Topical Binahong Leaf Extract in Modern Wound Care for Healing Diabetic Wounds in Modern Wound Care Homes Husada Prima Mandiri Mojokerto - Raras Merbawani; Nonse Hasan Ragil Saputri; asef wildan munfadlila (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
One of the diabetes mellitus syndromes is diabetic wounds. Diabetic wound treatment is good for preventing infection and amputation. Treatment of wounds that can heal wounds and develop at this time is modern wound care using topical therapy / modern clothing, where expensive costs require care that requires a large cost. Plants that can be used to heal wounds are leaves of binahong because they contain flavonoids, oleanolic acid, protein, ascorbic acid. and saponins. This study aims to determine topical treatment of leaf extract in modern treatments to treat diabetic wounds. The design of this study was a quasi experiment with a non equivalent control group design. The population in this study were people with diabetes mellitus with diabetic wounds at 34 Modern Husada Prima Mandiri Wound Care Homes. The sampling technique is consecutive sampling with a sample of 32 people. Data collection uses MANUAL BWAT. The results showed that the average score was lowest for groups (7.69 <8.00). The results of the analysis of researchers in groups were effective and effective diabetic wounds. This is because there are differences that are on average not too good for the second group (Difference 0.31). In addition, the average GDA, vascularization conditions and losses in the groups were worse with the control groups, where they could affect the wound. Ascorbic acid content and protein in binahong leaf extract help grow granulation tissue, support granulation tissue and accelerate epithelialization.